Catheter-Directed Middle Hemorrhoidal Artery Embolization for Life-Threatening Rectal Bleeding - Mubin I Syed; Najeeb Chaudhry; Azim Shaikh; Kamal Morar; Kumar Mukerjee; Earl Damallie (Canadian Journal of Gastroenterology)
Over the past 10 years, arteriography has become a well-established technique for the diagnosis of acute lower gastrointestinal bleeding, but not particularly for rectal bleeding. However, to the authors’ knowledge, the technique of middle hemorrhoidal artery embolization has rarely been reported in the literature. In the present report, three patients with life-threatening rectal bleeding are presented, which was controlled by superselective embolization of the middle hemorrhoidal artery or selective embolization of the internal iliac artery as a last resort.